Effects of lignin in nanocrystalline cellulose on mechanical, morphological and thermal properties of kenaf core-reinforced polypropylene composites - Sabaruddin, Fatimah Athiyah (2019)
The excessive application of chemicals during the NCC production led to harmful chemical discharge that can damage the environment. The process of NCC production can be shorten by excluding the bleaching process and retain partial of lignin within NCC. Lignin was found to be high in thermal stability as it was able to withstand high temperature up to 900 ˚C. Lignin also possess polar and non-polar groups in its chain network which make lignin as good compatibilizer. The implication of lignin in NCC surface has been reported, however its effect on the nanocomposites has not been discussed yet. Hence, if lignin can be retained in NCC and posing no significant adverse effect on the composites, it would give a new perspective in the NCC application. Therefore, in this study, NCC from KC was produced through the soda-AQ pulping process and the lignin content in NCC were varied via different sequence of bleaching. Four different pulps were produced from the bleaching process denoted as UB (unbleached pulps), B1 (bleached up to stage D1), B2 (bleached up to stage D2), and B3 (bleached up to stage D3). All pulps were proceeded with acid hydrolysis treatment to produce the NCCs. All NCCs were analysed having different lignin content which confirmed via chemical analysis and kappa number test. The thermal analysis shows that, the NCC of high lignin content was not able to resist early thermal degradation temperature but was able to withstand a temperature up to 700 ℃ with highest amount of residual char. The NCCs (0.5 and 1 wt. %) then were incorporated within kenaf core reinforced polypropylene (PP/KC) composites with addition of 1 wt % of maleic anhydride grafted polypropylene (MAPP) and its effect on physical, chemical, mechanical, and thermal properties were determined. Overall, the presence of lignin in NCC help to improve the thermal stability of the nanocomposites with marginal effect on the mechanical properties. Furthermore, post alkaline treatment were done upon NCC having different bleaching condition to remove the remaining sulphates as by-product of acid hydrolysis process. However, post alkaline treatment were analysed to be unnecessary for unbleached NCC as it did not give any significant effect to the properties of the NCC and the nanocomposites.